OBJECTIVES AND CHAPTER SCHEME OF THE MAHARASHTRA PUBLIC TRUST ACT, 1950 (International Journal of Food and Nutritional Sciences, 2022)
The Maharashtra Public Trusts Act is the piece of legislation that governs public trust in the state of Maharashtra. The Bombay Public Trusts Act, 1950 was renamed The Maharashtra Public Trusts Act by the Maharashtra state with retroactive effect beginning on May 1, 1960. The Act's goal is to provide appropriate rules for the efficient management of public religious trusts and charity trusts in the territory governed by the State of Bombay. In addition, it is in the nature of the sensible person to control and create better rules for the administration of public religious and charitable trusts in the State of Bombay. The research paper includes a fundamental framework, goals, and purpose of the Maharashtra Public Trusts Act.